Optimization of recovery processes for athletes using bioenergy means - Bakaev V.V.; Punich S.V.; Vasilyeva E.A.; Ponimasov O.E. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assessment of the influence of bioenergetic exercises on the recovery process of track and field athletes specializing in 400 m running. Methods and structure of the study. The experimental group consisted of 16 male athletes specializing in 400 m running at the age of 20,3 ± 1,5 years. The anaerobic glycolytic load corresponded to performing the main competitive exercise three times. During recovery periods between training tasks, bioenergetic recovery agents were used. Bioenergetic indicators characterizing the intensity of adaptation processes to the training load were recorded. Results and conclusions. It has been established that the use of bioenergetic exercises during the recovery process accelerates the decrease in heart rate and oxygen consumption without causing accelerated removal of lactate from the blood plasma. The results of changes in heart rate and oxygen consumption indicate that bioenergetic exercise has a positive effect on the recovery processes of athletes.